Korelasi antara Kesiapan Teknologi dengan Persepsi Kemudahan pada Pengguna Aplikasi Mobile JKN - Ibrahim, Mochammad Malik; Titis Eka Gusti; Ayu Wulandari (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
The Mobile JKN application was developed to facilitate participants in accessing digital health services, but its utilization is still low due to limited user technological readiness. This study aims to analyze the correlation between technological readiness and perceived ease of use among Mobile JKN users at Prof. Dr. Soekandar Regional General Hospital, Mojokerto Regency in 2025. The study population was 3,094 users with a sample of 354 respondents selected through a purposive sampling technique. This study used a quantitative, correlative analytical design with a cross-sectional approach. The instrument was a questionnaire based on the Technology Readiness Index (TRI) and the Technology Acceptance Model (TAM). The results showed that most respondents had a moderate level of technological readiness and perceived ease of use, and there was a significant correlation between the two variables. The conclusion of this study is that the higher the technological readiness, the higher the perceived ease of use of Mobile JKN. Efforts to improve this can be done through socialization activities at least twice a month to strengthen participant digital literacy.